Systemic Racism Affecting Latinx Population Health During the COVID-19 Pandemic and Beyond: Perspectives of Latinx Community Health Workers and Community-Based Organization Leaders (Mary Ann Liebert, 2023)
Introduction: The purpose of this study is to identify forms of systemic racism experienced by Latinx communities in North Carolina during the COVID-19 pandemic as identified by Latinx community health workers (CHWs) and community-based organization (CBO) leaders. Methods: We conducted three focus groups in July 2022 (N=16). We performed qualitative analysis of data using an iterative inductive approach of the original language in Dedoose. Results: Four central themes emerged: (1) Access to resources for Latinx individuals; (2) Immediate, transitional, and future fears; (3) Benefits of CHWs; and (4) Lessons learned. Discussion: Institutional and state policies often do not involve community members, such as CHWs and CBO leaders, at the start of the development process, leading to ineffective interventions that perpetuate health disparities and systemic racism. Health Equity Implications: Community-informed policy recommendations can improve alignment of community and policy priorities to create more effective interventions to address systemic racism and promote health equity.